Laboratory Manual for Mohs Micrographic Surgery Frozen Tissue Processing - McKay, Camille; Nehal, Kishwer S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This manual provides a thorough and up-to-date reference on the Mohs tissue processing technique. Mohs micrographic surgery is a distinct surgical and tissue processing technique that allows comprehensive margin control for high-risk skin cancers with the highest cure rate. Mohs micrographic surgery entails expertise in Mohs tissue frozen section processing in a fully licensed Mohs laboratory. Laboratory Manual for Mohs Micrographic Surgery Frozen Tissue Processing provides extensive practical guidance on optimal management from the leading experts in the field including perspectives from Mohs technicians, laboratory managers, Mohs surgeons and regulatory affairs. It covers the Mohs lab training curriculum for technicians and Micrographic Surgery and Dermatologic Oncology fellows and therefore is an extremely valuable resource for any healthcare professional in the Mohs micrographic surgery field.
Introduction/Mission Statement -- History of Mohs Surgery -- Accessioning and Labelling -- Mapping, Inking and Orientation -- Embedding -- Microtomy -- Staining and Coverslipping -- Special site surgery tissue processing techniques -- Immunohistochemistry -- Pitfalls in processing -- Daily Maintenance and Decontamination process -- Handling and storage of Hazardous and Non-hazardous -- Lab design, equipment, staffing, workflow -- Ergonomics -- Regulatory Standards and Importance of Quality Assurance.
Keywords: Dermatology; Dermatology